Fighting transitions of soldiers to enemy in the Civil War: the view of the White Army corps commander - A. V. Posadskiy (Омский научный вестник: Серия "Общество. История. Современность")
The archaeographic work aims to present the struggle of the White Army command in the East with the transitions of individual servicemen and entire units to the enemy at the end of June – beginning of July 1919 by the example of two orders of the commander of the 11th Yaitsky Corps of the Southern Army. These newly published documents, revealed in the funds of the Russian State Military Archive, reveal the White command’s understanding of the nature of this negative phenomenon and the logic of combating it. The theoretical basis of the study is the combination of the principle of consistency and an anthropological approach; this made it possible to present the published sources as part of counterintelligence measures in the white army, linking their appearance with specific personalities.